Principles of economics - Coppock, Lee (W.W. Norton, 2014)
An innovative instructor uses his tested insights and successful teaching practices to create a truly student-centered approach: real-world examples, pedagogy developed in his own classrooms, and problem solving tools that resonate with today’s students